PERANCANGAN APLIKASI SISTEM UJIAN ONLINE BERBASIS ANDROID DI TINGKAT UNIVERSITAS - Danny Fachrul Hakim; Aliyadi Aliyadi; Andy Triyanto (Universitas Muhammadiyah Ponorogo, 2019)
Given the importance of an exam within the university, it is expected that a media can be easily accessible and easy to use by students or lecturers in conducting exams. On the other hand the media must have efficiency that support the execution of the test, such as time efficiency, energy efficiency, resource efficiency and efficiency in the delivery of information. Application is software that is made with the aim to serve human needs in various fields of activity such as in economics, government, education and other areas related to human life. Android is a Linux-based operating system designed for mobile devices such as smart phones and tablet computers that are currently widely used by people around the world. Therefore, using the Android-based application media is expected to assist the parties involved in the execution of the exam in order to carry out the test easily and efficiently. Waterfall method is a method used in the design of this application. The programming language used in the design of this application is the Java programming language and PHP. For application database using MySQL. After testing with black box method can be concluded that this application has been running in accordance with what is expected. The results of this study are exam applications that can display the exam in the form of exam questions and answer options and can enter the participants' answers easily. This app also comes with an exam supervisor feature that is used to crack down on cheating in exams. Students can also directly see the results of the exam after the exam is done.